PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI) - Dewi Susanti (2013)
This study was conducted to examine the effect of variable Capital Employeed Efficiency, Human Capital Efficiency, Structural Capital Efficiency on Profitability in the banking company in Indonesia Stock Exchange in 2011. The population number of 27 companies are banking on the Indonesia Stock Exchange in 2011. The data is obtained from the published financial statements of the companies with a total 27 companies. Purposive sampling method is being used in the sample selection. The type of data in this study is secondary data obtained from idx.co.id. The analysis technique that used in this study is multiple linear regression and hypothesis testing using the F-statistic and t-statistics with a confidence level of 5%. The results showed that Capital Employeed Efficiency, Human Capital Efficiency, Structural Capital Efficiency are simultaneously giving a significant effect on Profitability. In partial, the Capital Employeed Efficiency has no effect on Profitability, while Human Capital Efficiency and Structural Capital Efficiency partially have a significant effect on Profitability.